2003
DOI: 10.1007/s00592-003-0086-y
|View full text |Cite
|
Sign up to set email alerts
|

Body mass index and skinfold thickness versus bioimpedance analysis: fat mass prediction in children

Abstract: Childhood obesity increases the risk of morbidity whether or not obesity persists into adulthood. Measurement of body fat content using bioimpedance analysis (BIA) is a useful tool in epidemiologic studies. Both tricep skinfold thickness (TST, mm) and body mass index (BMI, kg/m(2)) are indirect, simple methods and easy to perform for assessing body composition. These methods are generally accepted as good clinical measures for defining childhood obesity. The aim of our study was to evaluate fat mass (FM, kg an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
36
0
5

Year Published

2006
2006
2016
2016

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 60 publications
(44 citation statements)
references
References 10 publications
3
36
0
5
Order By: Relevance
“…Pecoraro et al (2003) also showed a significant positive correlation between fat mass measured by BIA and BMI (r ¼ 0.92; Po0.001). The sensitivity and specificity of BMI in low-percent body fat subjects were calculated by Gartner et al in 586 women of Congo, Central Africa.…”
Section: Discussionmentioning
confidence: 75%
See 2 more Smart Citations
“…Pecoraro et al (2003) also showed a significant positive correlation between fat mass measured by BIA and BMI (r ¼ 0.92; Po0.001). The sensitivity and specificity of BMI in low-percent body fat subjects were calculated by Gartner et al in 586 women of Congo, Central Africa.…”
Section: Discussionmentioning
confidence: 75%
“…Hence, it is prudent to make the diagnosis of obesity based on the measure of percentage body fat. BIA method is a useful, available, inexpensive, valid and reliable technique in nutritional epidemiologic studies on both healthy subjects (Blanchard et al, 1990;Roubenoff, 1996;Pecoraro et al, 2003) and patients monitoring in medical settings and clinics (Ellis et al, 1999;Lukaski, 1999;Erselcant et al, 2000) for body composition analysis and investigating obesity and overweight prevalence.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, if variations in compressibility reflect differences in the fluid content of uncompressed skinfolds, the reduction of these differences by compression might increase the validity of skinfold thicknesses as measures of regional fatness. Anthropometry and BIA measurements are relatively simple techniques that have correlation with the amount of body fat; [14][15][16] therefore, they are widely used in epidemiological studies. [15][16][17][18] BIA aims to estimate the total body water, and then the fat-free mass.…”
Section: Discussionmentioning
confidence: 99%
“…V současnosti patří k nejvíce využívaným přístrojové metody založené na principu biolektrické impedance (BIA), které jsou využívány pro diagnostiku tělesného složení, jednotlivých frakcí a kompartmentů. Hodnocení složení těla pomocí metody BIA nachází své praktické uplatnění v mnoha ob-lastech lékařské i sportovní praxe (Buchholz, Bartok, & Schoeller, 2004;Jaff rin, 2009;Malina, Bouchard, & Bar-Or, 2004;Pecoraro et al, 2003). Především v posledním desetiletí dochází k intenzivnímu rozvoji metody a s je tím spojený i vývoj moderní přístrojové techniky (Ward, 2012).…”
Section: úVodunclassified